«Հիշարժան տարեթվերը»՝ որպես մեթոդ-մատենագիտական ձեռնարկ - Հովհաննիսյան, Մարի (Հայաստանի ազգային գրադարան / National Library of Armenia, 2023)
The National Children’s Library after Khnko Aper, is the methodical center of children’s libraries of our country, carries out various methodological-bibliographic publishing works. From 1963 up to now, the library’s Bibliography Department has been creating a “Memorable Dates” reference manual, which includes the famous dates of the given year, commemorative books and works, national and international holidays, as well as topics of interest to children and young readers. It helps different levels of society plan their work and organize events and book exhibitions. Encyclopedias, biographical dictionaries, relevant reference books, official websites on the online platform, etc. are used in compiling the manual.
Բանբեր Հայաստանի գրադարանների ։ Գիտամեթոդական հանդես ։ Հատուկ թողարկում / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2023 ․- էջ 154 - 156
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն